2020
DOI: 10.1177/2058460119900435
|View full text |Cite
|
Sign up to set email alerts
|

CT imaging of the Eustachian tube using focal contrast medium administration: a feasibility study in humans

Abstract: Background: Several methods of imaging the Eustachian tube have been tested in the last century, although neither has led to an established method. The introduction of balloon Eustachian tuboplasty (BET) has revived the request for Eustachian tube (ET) visualization in patients with chronic Eustachian tube dysfunction. Many institutions perform preoperative computed tomography (CT) scans of the temporal bone and epipharynx before BET. Purpose We hypothesize that the injection of a contrast medium into the tymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The ET lumen path length can be measured from cadaveric specimens, which were finely sectioned and 3D reconstructed to account for the curvature of the ET at the bony cartilaginous junction [ 6 ]. The measurement of ET lumen path length is not possible on CT scans unless under special circumstance such in patients with patulous ET [ 11 ], or with invasive injection of contrast media into the middle ear cleft [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ET lumen path length can be measured from cadaveric specimens, which were finely sectioned and 3D reconstructed to account for the curvature of the ET at the bony cartilaginous junction [ 6 ]. The measurement of ET lumen path length is not possible on CT scans unless under special circumstance such in patients with patulous ET [ 11 ], or with invasive injection of contrast media into the middle ear cleft [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased availability of high-resolution temporal bone computed tomography (CT) and the use of cone-beam CT, combined with the advent of multiplanar reconstruction (MPR) has made it possible for ETs to be measured on imaging studies [ 1 3 , 10 , 11 ]. A review of the literature revealed a range of methods in measuring ET angle and lengths, as summarised in Table 1 .…”
Section: Introductionmentioning
confidence: 99%